A Study of Perceived Managerial Competencies in the Telecommunication Industry: a Malaysian Perspective - Yeo, Amy Chu May (1999)
This study was conducted with the aim of providing an insight into the competency study from the Malaysian point of view, in general, and telecommunication industry, in particular. Specifically, it is the objective of this study to identify a list of competency elements and to determine whether they are necessary or important for manager to perform their managerial jobs. Four hypotheses were formulated to achieve the objectives of the study. The four hypotheses were: 1) Managers do not perceive generic competencies to be necessary in carrying out their jobs, 2) There is no significant variation of competency elements across managerial levels, 3) There is no significant variation of competency elements across functional areas, 4) There is no significant variation of competency elements across organisations in the industry. Data for this study has been collected primarily through structured questionnaires. The ninety-one competency elements used in this study were based on the questionnaire developed by Hunt and Wallace (1997). Analysis of the data was performed using the Statistical Package for Social Science (SPSS). Several statistical tools such as descriptive analysis, factor analysis, analysis of variance and bonferroni post-hoc multiple comparison were used to analyse the data. The major findings are as follows: Using descriptive analysis, the mean score for the ninety-one competency elements were ranked according to descending order. The findings indicated that managers perceived all the ninety-one competency elements as necessary for them to perform their jobs. Of the nine-one competency elements, more than 80% of the elements were perceived as necessary, pointing to the generic nature of the managerial competencies. Thus, Hypothesis 1 was supported. From the twenty-three highly rated competencies, factor analysis produced a five dimensional competency model. These five dimensions were categorised into 1) problem solving, 2) personal management, 3) communication and integrity, 4) organisation knowledge, 5) image and direction. Statistical tools such as ANOVA and Bonferroni Post Hoc multiple companion were used to determine variation of competency elements across managerial levels, functions and between organisations. From the analysis, it was evidenced that there were variations across managerial levels. Nine (39%) out of twenty-three elements were significantly varied between top and lower level managers. Thus, the hypothesis 2 was less than partially supported. Some significant results were also shown pertaining to the variation of competency elements across functional areas. Out of the twenty-three elements, six elements (26%) were significantly varied. The hypothesis 3 was less than partially supported. In addition, the analysis produced significant results between organisations in the industry. A total of fifteen (65%) out of twenty-three competency elements were significantly varied. Thus, hypothesis 4 was partially supported. The current study is timely and of importance especially to managers in the telecommunication industry. They could utilise the competency model for managing human resources such as in recruitment and selection, training and development, and performance appraisal. The findings could also provide further information on the usefulness and value of the generic competency model of Hunt and Wallace and it could further widen the applicability of the generic competency model across culture and industry.